2003
DOI: 10.1152/ajpendo.00289.2003
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous angiotensin induces brain c-fosexpression and vasopressin release in the near-term ovine fetus

Abstract: 2003.-The effect of intravenous angiotensin II (ANG II) on fetal brain c-fos expression and arginine vasopressin (AVP) release was studied in the near-term ovine fetus. Fetuses with chronically implanted catheters received an intravenous infusion of ANG II or saline. Fetal plasma AVP concentrations were significantly increased after the peripheral administration of ANG II, with peak levels (3-fold) at 30 min after the intravenous infusion. There was no change in fetal plasma osmolality, sodium, and hematocrit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…AT1R and AT2R play an important role in cell growth, differentiation and apoptosis during development 1316 . Abnormal AT1R and AT2R expression in the renal system has also been shown to be related to kidney diseases 17,18 . However, the detailed mechanism underlying Ang II-induced renal tubular cell necroptosis and kidney injuries is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…AT1R and AT2R play an important role in cell growth, differentiation and apoptosis during development 1316 . Abnormal AT1R and AT2R expression in the renal system has also been shown to be related to kidney diseases 17,18 . However, the detailed mechanism underlying Ang II-induced renal tubular cell necroptosis and kidney injuries is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, several central regions, including the SFO, OVLT, and AP, lack a BBB, thus Ang II in the peripheral circulation can act on the brain via those central “windows”. In a recent study in the sheep, we demonstrated that intravenous Ang II can induce cellular activity marked with intensive c-fos expression in the SFO, OVLT, MnPO, SON, and PVN (Shi et al, 2003, 2004c). The peripheral Ang II acts on the fetal hypothalamus indirectly via the circumventricular organs (CVOs, such as SFO, OVLT in the forebrain) which lack the BBB, but are rich of Ang II receptors.…”
Section: Functional Development Of the Fetal Brain Rasmentioning
confidence: 83%
“…Moreover, as in fetal sheep (11), arterial ANG II infusions in the newborn hind limb do not elicit vasoconstrictor responses (17), suggesting that ANG II-induced pressor responses after birth occur through indirect mechanisms, e.g. release of AVP or catecholamines (34,35). However, Wilson et al (21) reported that increases in circulating ANG II after birth contributed to the increase in MAP.…”
Section: Discussionmentioning
confidence: 97%